The Characteristics of the Laminated Board of Oil Palm Trunk - Darwis, Atmawi; Massijaya, Muhammad Y; Nugroho, Naresworo; Alamsyah, Eka M (Jurnal Ilmu dan Teknologi Kayu Tropis, 2014)
The purpose of this study was to determine the physical and mechanical properties of glue laminated (glulam) of oil palm trunks lumber (OPTL) composed of different number of layers and trunk heights (2 m, 4 m, and 6 m). The number of layers was varied at 2, 3 and 4 layers with the thickness of lamina of 3 cm, 2 cm, and 1.5 cm, respectively. The results showed that the glulam of OPTL retained higher density and mechanical properties compared to those of its solid form. The properties of OPTL glulam decreased from the bottom to the top division of the trunk. The physical and mechanical properties of glulam increased with increasing layers. Modulus of Elasticity (MOE) of OPTL 4 layered glulam increased by more than 50% compared to that of its solid OPT. Isocyanate based adhesive used to produce the glulam resulted in a satisfied bonding indicated by 100% and 0% wood damage in shear and delamination test, respectively. The mechanical properties of OPTL glulam (MOE, MOR, and shear strength) failed to satisfy the requirement of Japan Agricultural Standard for Glued Laminated: No 1152 (2007).Keywords: glulam, laminae, oil palm trunk, physical-mechanical properties